Treadmill training protects valproic acid-induced autistic features via cerebellar AMPK/PPAR-γ dependent pathway and improves mitochondrial activity in mice - Anwaar M. Shaban; Omnia Ameen; Marwa Omar; Sara A. El Derbaly; Hend R. Omara; Asmaa I. Bayomi; Asmaa A. Abdel Latif; Zainab Ibrahim Elakabawy; Suzan A. Khodir (Scientific Reports)
Abstract Autism spectrum disorder (ASD) is a neurodevelopmental disorder associated with impaired sociality and stereotypic behavior. Endurance training could modulate mitochondrial dysfunction sharing in the pathophysiology of ASD. We investigated the neuroprotective effects of training on VPA-induced ASD in mice. Forty mice were divided into control, Training, VPA, and VPA + Training groups. Mice were subjected to neurobehavioral tests. Assessment of the protein content of serum CRP, irisin, meteorin-like protein (metrnl), cerebellar inflammatory markers, serotonin, and BDNF was done by ELISA. MDA and catalase were also investigated using a colorimetric technique. Cerebellar citrate synthase (CS) enzyme activity was also measured. Cerebellar AMPK, PPAR-ɣ, and metrnl gene expressions were assessed via RT-PCR. Cerebellar immunohistochemical studies of GFAP, Bax, and PPAR-γ markers were conducted. Statistical methods were used in the data analysis, including one-way ANOVA, and t-tests. The VPA group showed significant impairments in social interaction, and cognition in neurobehavioral tests (P = 0.000). A significant increase of CRP, MDA, and inflammatory markers associated with a significant reduction in irisin, metrnl, catalase, CS, serotonin, and BDNF (P = 0.000) was noticed. Besides, cerebellar AMPK and PPAR-γ gene expressions were down-regulated. Significant cerebellar degenerative changes were also observed (P = 0.000). Training dramatically reversed VPA-induced neurobehavioral, biochemical, and cerebellar degenerative changes. Endurance training has anti-inflammatory, anti-apoptotic, and antioxidant properties. Adipo-myokines release, enhanced mitochondrial activity, and activation of AMPK and PPAR-γ pathways could be involved mechanisms. Training programs are a promising strategy for addressing the social and neurobehavioral impairments linked to ASD, according to the muscle-brain interplay.